PENINGKATAN KEMAMPUAN MEMBACAKAN PUISI DENGAN LATIHAN TERBIMBING SISWA KELAS VIII SMP NEGERI 13 SEMARANG - Nia Ulfa Martha (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
This  study aims to  prove and know the  size of the  increase students’ ability  to  read poetry with  guided  exercises. This  study use  class  action research  (PTK) carried out  in  two stages, namely the cycle I and cycle II of SMP Negeri 13 Semarang. The variable form of the ability to read poetry and learning with guided exercises. Data collection on the first cycle and second cycle using the techniques in the form of deeds and nontest. Nontest technique used is observation.  The  resultshowed  learning  to  read  poetry  with  guided  exercises  to  enhance students’ ability to read a poem by it self. Assessmentbased on the acquisition of appreciation, vocal  technique,  and  appearance.  In  the  first  cycle  of  learning  students  achieve  an  average rating  of  52.60,  72.76  secong  cycle,  so  that  an  increase  of  20.116.  the  rsult  showed  an increase after learning to read poetry with guided exercises performed in class action cycle I adn  cycle  II  provides  a  fun  learning  experience  and  an  impressive  student.  With  the psychological state of these students, this learning can be carried out properly. Thus, the result of learning to read poetry to increase after learning to read poetry with guided exercises.This  study aims to  prove and know the  size of the  increase students’ ability  to  read poetry with  guided  exercises. This  study use  class  action research  (PTK) carried out  in  two stages, namely the cycle I and cycle II of SMP Negeri 13 Semarang. The variable form of the ability to read poetry and learning with guided exercises. Data collection on the first cycle and second cycle using the techniques in the form of deeds and nontest. Nontest technique used is observation.  The  resultshowed  learning  to  read  poetry  with  guided  exercises  to  enhance students’ ability to read a poem by it self. Assessmentbased on the acquisition of appreciation, vocal  technique,  and  appearance.  In  the  first  cycle  of  learning  students  achieve  an  average rating  of  52.60,  72.76  secong  cycle,  so  that  an  increase  of  20.116.  the  rsult  showed  an increase after learning to read poetry with guided exercises performed in class action cycle I adn  cycle  II  provides  a  fun  learning  experience  and  an  impressive  student.  With  the psychological state of these students, this learning can be carried out properly. Thus, the result of learning to read poetry to increase after learning to read poetry with guided exercises.